Η επανάσταση του Nικ. Φωκά και του Νικ. Ξιφία (1021-1022): η τελευταία εσωτερική κρίση στη βασιλεία του Βασιλείου Β΄ (976-1025) - ΤCHKOIDZE, Eka (Byzantina Symmeikta, 2015)
The Phokas-Xiphias Revolution was the third and the last revolution of the age-long reign of Basil II the Bulgar-slayer, led by two renowned generals, Nikephoros Xiphias and Nikephoros Phokas. It broke out in Cappadocia in 1022 with the purpose to overthrow the Byzantine Emperor.  Medieval narratives that relater these events written in Greek, Arabic, Georgian, or Armenian, all agree that this insurrection was extremely serious. It involved a large number of rebels within the empire and the insurrectionists were widely believed to be in contact with forces outside the empire, including the Georgian king George I (1014-1027). The revolution broke out when the military conflict between Byzantium and Georgia was still ongoing. Some Georgians including the noble Pheris were actively involved in it. In this article all existing sources on this issue are analyzed. An emphasis is given on the causes of the  revolution and its consequences on the Empire’s foreign policy.